ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN DI PT. ABC BATAM - Shinta Wahyu Hati (Politeknik Negeri Batam, 2020)
This study was conducted to determine whether there are factors that affect employee turnover Intenton at PT ABC Batam. The data analysis method used in this study is to use the Structural Equation Modeling (SEM) method using the SmartPLS application. The number of samples used in this study is the same as the total population of 93 people consisting of administrative employees and permanent employees. The data collection in this study used a questionnaire (questionnaire) consisting of 5 exogenous variables and 1 endogenous variable, namely Turnover Intention. The results of the study are only 2 variables that have an influence on turnover intention, namely the variable of leadership and satisfaction. While the compensation variable, organizational culture and career development do not affect Turnover Intention which is indicated by the t-value greater than t-table (1.66)